Analisis implementasi kebijakan penjualan kredit dan pengendalian risiko kredit dalam upaya meningkatkan profitabilitas (Studi pada PT Trakindo Utama Manado) - Mamahit, Debora Cindy; Karamoy, Herman; Kalalo, Meily Y. B. (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study examines the implementation of credit sales policies and credit risk control and their influence on profitability at PT Trakindo Utama Manado. Maintaining profitability amid credit-based transactions is essential for the company’s financial stability. This research adopted a qualitative method with a case study approach, in which data were collected through in-depth interviews and documentation. The results reveal that the company’s credit sales policy, conducted through leasing partners, however, the segregation between sales and collection functions remains incomplete. The primary risks identified include payment delays and customer defaults, which are mitigated through preventive, detective, and corrective actions based on the 5C credit principles (Character, Capacity, Capital, Collateral, and Condition). The study recommends stricter adherence to credit procedures, clearer separation of duties, and deeper assessment of the Capital and Condition criteria to strengthen cash flow, minimize risk, and sustain profitability. This research contributes to the literature on the nexus between credit policy, risk management, and financial performance within Indonesia’s heavy equipment industry.